Effectiveness of foot skin protection technology in elderly patients with diabetic peripheral neuropathy - Zhou, Lin; Song, Pin-Fang; Qin, Wen; Jia, Qing; Miao, Fei; Bai, Jiao-Jiao (Frontiers in Endocrinology, 2024)
Objective: The aim of this study is to assess the effectiveness of foot skin protection technology in elderly patients with diabetic peripheral neuropathy. Methods: The foot skin protection technology was developed based on a comprehensive literature review and preliminary research conducted by our research team. Subsequently, 88 elderly patients with diabetic peripheral neuropathy and experiencing foot skin problems were recruited from two community health service centers in Shanghai. Using a random number table, the participants were randomly assigned to either the control group or the experimental group. Patients in the experimental group received foot skin protection technology interventions, while those in the control group received standard community nursing guidance for a duration of 3 months. The incidence, severity, and discomfort associated with foot skin problems were evaluated before and after the intervention period in both groups. Results: The incidence, severity, and discomfort of foot skin problems notably reduced in the experimental group (all P < 0.05). Conclusion: The foot skin protection technology demonstrates significant potential in enhancing foot skin condition.